Low-level expression of SAMHD1 in acute myeloid leukemia (AML) blasts correlates with improved outcome upon consolidation chemotherapy with high-dose cytarabine-based regimens - Rassidakis, Giorgios; Schaller, Torsten (Blood cancer journal, 2018)
Sterile alpha motif and histidine/aspartic acid domain containing protein 1 (SAMHD1) limits the efficacy of cytarabine (ara-C) used in AML by hydrolyzing its active metabolite ara-CTP and thus represents a promising therapeutic target. SAMHD1 has also been implicated in DNA damage repair that may impact DNA damage-inducing therapies such as anthracyclines, during induction therapy. To determine whether SAMHD1 limits ara-C efficacy during induction or consolidation therapy, SAMHD1 protein levels were assessed in two patient cohorts of de novo AML from The University of Texas MD Anderson Cancer Center (USA) and the National University Hospital (Singapore), respectively, using immunohistochemistry and tissue microarrays. SAMHD1 was expressed at a variable level by AML blasts but not in a broad range of normal hematopoietic cells in reactive bone marrows. A sizeable patient subset with low SAMHD1 expression (<25% of positive blasts) was identified, which was significantly associated with longer event-free (EFS) and overall (OS) survival in patients receiving high-dose cytarabine (HDAC) during consolidation. Therefore, evaluation of SAMHD1 expression level in AML blasts at diagnosis, may stratify patient groups for future clinical trials combining HDAC with novel SAMHD1 inhibitors as consolidation therapy.
Gesehen am 24.04.2019